Fetal Acetylcholine Receptor Inactivation Syndrome and Maternal Myasthenia Gravis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Three brothers with facial diplegia and a myasthenic mother are reported from McGill University, Canada; University of Oxford, UK; and Columbia University, New York.